2015
DOI: 10.2147/ppa.s71535
|View full text |Cite
|
Sign up to set email alerts
|

Patient considerations in the treatment of COPD: focus on the new combination inhaler umeclidinium/vilanterol

Abstract: Medication adherence among patients with chronic diseases, such as COPD, may be suboptimal, and many factors contribute to this poor adherence. One major factor is the frequency of medication dosing. Once-daily dosing has been shown to be an important variable in medication adherence in chronic diseases, such as COPD. New inhalers that only require once-daily dosing are becoming more widely available. Combination once-daily inhalers that combine any two of the following three agents are now available: 1) a lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Nonadherence to treatment may negatively influence the effectiveness of the triple therapy regimen and may result in the worsening of clinical symptoms or other poor health outcomes 29. Problems with medication adherence among patients with COPD have been well documented worldwide 3539. Dhamane et al, using a large administrative claims database (N=14,117; mean age, 69.9 years), observed that 79.2% of patients were nonadherent to maintenance COPD medications with a mean PDC of 0.47 40.…”
Section: Discussionmentioning
confidence: 99%
“…Nonadherence to treatment may negatively influence the effectiveness of the triple therapy regimen and may result in the worsening of clinical symptoms or other poor health outcomes 29. Problems with medication adherence among patients with COPD have been well documented worldwide 3539. Dhamane et al, using a large administrative claims database (N=14,117; mean age, 69.9 years), observed that 79.2% of patients were nonadherent to maintenance COPD medications with a mean PDC of 0.47 40.…”
Section: Discussionmentioning
confidence: 99%
“…42 Among studies that investigate vilanterol/umeclidinium combination therapy, increased HR was observed in the treatment group (by 4.8 bpm). 39,56 A study by Donohue JF et al also observed some differences among subjects discontinued from the study, where abnormalities in ECG or Holter monitoring was twice as high in treatment than placebo groups. 39 However, a study by Hanania NA et al found that vilanterol monotherapy was not associated with significant changes in QTc interval or vital signs among COPD patients, even with increased doses.…”
Section: Vilanterolmentioning
confidence: 97%
“…[42][43][44] Studies have found that vilanterol has low bioavailability, where only 27% of vilanterol was absorbed when given as a combination product with umeclidinium. 56,57 After a once daily inhaled dose, C max was reached after 5-15 minutes, half-life was 11 hours, and steady state developed after 6 days. 57 The Vilanterol/fluticasone combination was found to be effective in reducing asthma exacerbations by 24% compared to fluticasone alone, whereas the once a day dosing was believed to be able to improve compliance and disease control.…”
Section: Vilanterolmentioning
confidence: 99%
“…Inhaled corticosteroids (ICS) play an essential role on anti-inflammation, and beta 2 -agonists stimulate beta 2 -adrenergic receptors in order to relax airway smooth muscle. Combination of ICS and long-acting beta 2 -agonists (LABA) such as budesonide/formoterol and fluticasone/ salmeterol has effective synergistic action on improving symptoms, lung function, and life quality, as well as reducing exacerbation of COPD [15, 16]. Compared with fluticasone/ salmeterol, short-term treatment of budesonide/formoterol have a more rapid onset of action and improves pulmonary function and morning activities more greatly [17].…”
Section: Introductionmentioning
confidence: 99%